“An Automaton of Duty”? Some Remarks on Nietzsche’s Kant-Critique - Ondřej Sikora (Filozofia)
Friedrich Nietzsche belongs to the sharpest opponents of Kant’s practical philosophy. From his naturalistic perspective he subjects Kant to an uncompromising, gradually sharpening critique. The paper concentrates on selected aspects of this critique and asks a simple question, namely whether Nietzsche’s direct anti-Kantian passages contribute anything relevant to a substantive discussion of the core of Kant’s practical philosophy. Therefore, the interpretation focuses on Nietzsche’s direct references to selected motifs of Kant’s ethics with the aim of identifying the substantive core hidden behind the rhetorical expressions. This core refers to the four motifs that structure the interpretation: 1. duty, 2. imperative, 3. autonomy, and 4. the intelligible world. I argue for a negative answer to the main question, but at the same time I try to show not only a specific proximity of the two concepts of autonomy but also the possibility of understanding Nietzsche’s “autonomy of the body” as a continuous extension of the autonomy of pure will.